Changes of adiponectin and its receptors in rats following chronic renal failure. (February 2014) - Yu, Yan; Bao, Bai-jun; Fan, Ya-ping; Shi, Lan; Li, Shao-qing
Abstract Objective: To investigate changes of adiponectin and its receptors (Adipo R) in rats following chronic renal failure. Methods: Male SD rats were randomly divided into two groups: control group and chronic renal failure (CRF) group. The CRF group were gavaged with adenine (300 mg/kg/d) for 4 weeks and the control group with drinking water. All rats were anesthetized at 2nd or 4th week and blood and urine samples were collected for detection of renal function, 24 h urine protein and adiponectin concentration. Renal tissues were also collected for HE staining, immunohistochemistry and RT-PCR screening. Results: Compared with control group, the serum concentrations of urea and creatinine, 24 h urine protein excretion in the CRF group were significantly higher at 2nd week and further increased at 4th week (p < 0.05). The adiponectin levels in serum and urine in the CRF group were significantly higher than those of control group (p < 0.01). The renal expressions of Adipo R1 and Adipo R2 in CRF group were also significantly increased compared to control group (p < 0.01). The increased expressions of Adipo R1 and Adipo R2 were positively related to the adiponectin levels in serum, urine, and 24 h urine protein. Conclusion: The significant changes in expression of adiponectin and its receptors in rat CRF model could be an adaptive response that may provide the basis to understand pathological changes in chronic kidney disease.